Hip muscles strength and activation in older fallers and non-fallers - Morcelli, Mary Hellen [UNESP]; Crozara, Luciano Fernandes [UNESP]; Rossi, Denise Martineli [UNESP]; LaRoche, Dain Patrick; Marques, Nise Ribeiro [UNESP]; Hallal, Camilla Zamfolini [UNESP]; Castro, Alex [UNESP]; Cardozo, Adalgiso Coscrato [UNESP]; Goncalves, Mauro [UNESP]; Navega, Marcelo Tavella [UNESP] (Ios Press, 2014)
BACKGROUND: Hip muscles dysfunction may challenge postural control mechanisms and compromise the individual in imbalance situations.OBJECTIVE: To compare hip muscles strength, power and activation between older female fallers and non-fallers.METHODS: Forty-four older adult women (60-85 yr) were divided into two groups based on having falling or not in the period of one year before evaluation, fallers (n = 20) and non-fallers (n = 24). Isokinetic strength and power were assessed during hip flexion, extension, abduction and adduction movements, while EMG signals were recorded from the internal oblique (IO), rectus femoris (RF), multifidus (MU), gluteus maximum (GM), and biceps femoris (BF).RESULTS: Fallers had significantly lower extension (p = 0.033), abduction (p = 0.001) and adduction (p = 0.002) strength as well as significantly lower power in hip flexion (p = 0.028), extension (p = 0.005) and abduction (p = 0.002) compared to non-fallers. Non-fallers had 27.4% greater activation of RF (p = 0.005) during hip flexion and 37.9% higher coactivation of IO/MU during hip abduction (p = 0.003). Significant linear regression was found between hip extension strength and GM and BF activation in both groups.CONCLUSION: Hip muscles strength and activation may increase the risk of falling in older women.
Keywords: Hip; aged; muscle strength dynamometer; accidental falls